An outbreak of acute respiratory disease caused by HAdV‐55 in Beijing, China, 2020. Issue 12 (30th August 2022) - Liu, HongBo; Li, Qingfeng; Xiang, Ying; Li, Hong; Liu, Kangkang; Du, Xinying; Yang, Chaojie; Liu, Hongbo; Shi, Mengjing; Hu, Xueqian; Wang, Hui; Zhang, Xiaohong; et al.
Abstract: Human adenoviruses (HAdVs) can cause acute respiratory diseases (ARDs) worldwide, and HAdV‐55 is a reemergent pathogen in recent years. In the study, we investigated an outbreak of ARD at a school due to HAdV‐55 in Beijing, China, during the early outbreak of coronavirus disease 2019 (COVID‐19). The epidemic prevention team was dispatched to the school to collect epidemiologic data and nasopharyngeal samples. Then, real‐time reverse transcription polymerase chain reaction (PCR) and multiplex PCR assays were used to detect severe acute respiratory syndrome coronavirus 2 and other respiratory pathogens, respectively. One representative HAdV‐55 isolate was selected and submitted for whole‐genome sequencing using a MiSeq system and the whole‐genome phylogenetic tree was conducted based on the maximum likelihood method. The outbreak lasted from January 27 to February 6, 2020, and 108 students developed fever, among whom 60 (55.56%) cases were diagnosed with HAdV‐55 infection in the laboratory using real‐time PCR and 56 cases were hospitalized. All the confirmed cases had a fever and 11 cases (18.33%) presented with a fever above 39°C. Other main clinical symptoms included sore throat (43.33%) and headache (43.33%). We obtained and assembled the full genome of one isolate, BJ‐446, with 34 761 nucleotides in length. HAdV‐55 isolate BJ‐446 was 99.85% identical to strain QS‐DLL, which was the first HAdV‐55 strain in China isolated from an ARD outbreak in Shanxi in 2006. One and four amino acid mutations were observed in the hexon gene and the coding region of L2 pV 40.1 kDa protein, respectively. We identified the first HAdV‐55 infection associated with the ARD outbreak in Beijing since the emergence of COVID‐19. The study suggests that improved surveillance of HAdV is needed, although COVID‐19 is still prevalent in the world.